SnoRNAs are involved in the progression of ulcerative colitis and colorectal cancer. Issue 5 (May 2017) - Yang, Xiao; Li, Yiming; Li, Lianyun; Liu, Juan; Wu, Min; Ye, Mei
Abstract: Background and aim: Emerging evidences indicate that small nucleolar RNAs (snoRNAs) are important regulatory molecules involved in various pathophysiological processes including inflammation and cancer. In the current study, we investigate whether snoRNAs dysregulate in colorectal cancer (CRC) and intestinal inflammation and contribute the pathogenesis of CRC. Methods: We analyzed the snoRNAs expression profile in CRC patients by GeneChipR Array and validated candidate snoRNAs expression in 44 CRC tissues, as well as in 28 ulcerative colitis (UC) and 28 healthy controls using reverse transcription quantitative polymerase chain reaction. Furthermore, we analyzed the correlation between snoRNAs expression and clinical characteristics of CRC and evaluated the diagnosis and differentiation efficiencies of the snoRNAs in CRC and UC. Results: The expression of snoRA15, snoRA41 displayed increased, whereas snoRD33 was down-regulated in CRC compared with matched non-cancerous tissues. When compared to healthy control, the three snoRNAs are all upregulated in lesion tissue of UC and CRC, which showed an increasingly trend from healthy control to UC and CRC. Conclusions: The identified three snoRNAs might contribute the carcinogenesis of colorectal cancer and involve in the progress from chronic intestinal inflammation to malignant tumor.